Is there a new round of regionalism in Central Asia? Content analysis of the texts of documents and Presidents’ speeches during the IV consultative meeting in 2022 - Mukasheva, З.Е.; Akhmedyanova, Д.К. (Bulletin of the L.N. Gumilyov Eurasian National University. Political Science. Regional Studies. Oriental Studies. Turkology Series., 2024)
In 2022 during the IV Consultative Meeting of the Heads of States of Central Asia the Treaty of Friendship, Good-Neighborhood and Cooperation for the Development of Central Asia in the 21st Century was signed. This fact indicates the deepening of cooperation between the Republics of Kazakhstan, Kyrgyzstan, Tajikistan, Turkmenistan and Uzbekistan, as well as the possible emergence of a new round of regionalism in Central Asia. This article presents a content analysis of the treaty texts, the joint statement of the heads of Central Asian states and presidents’ speeches of the republics, through which the key priorities in the field of cooperation for the countries of the region are identified. The results of the empirical research show that regional cooperation and security-related issues remain priorities for the Central Asian countries. The article consists of the following sections: introduction, theoretical part devoted to the processes of regionalism, literature review on the topic of regional integration in Central Asia, detailed description of the research methodology, discussion of the results and conclusions, as well as briefly highlighted current trends in the development of cooperation between the countries of the region.